Multiplication, histodifferentiation and regeneration of embryogenic cell suspensión on the plantain cultivar ‘Navolean’ (AAB) - Manuel Cabrera; Jorge López; Rafael Gómez-Kosky; Nery Montano; Maritza Reyes; D. Reinaldo; José de la C. Ventura; Victor Medero; Arletys Santos; M. García; Milagros Basail; E. Espinosa (Biotecnología Vegetal, 2002)
The results obtained show that the best cell density for the multiplication of the cell suspensions in the cultivar ‘Navolean’ is 3.0% settled cell volume. In the histo-differentiation phase the greatest formation of somatic embryos in the globular stage was obtained using a density of 12.0% final cell volume in liquid culture medium. The maturation of the embryos and an increase in germination was possible on using 0.5 gFW of somatic embryos during 30 days in the maturation culture medium. Using temporary immersion systems with 0.5 gFW of mature somatic embryos, the germination value was increased to 77.40%